Lactobacillus delbrueckii subsp. lactis (strain CIDCA 133) stimulates murine macrophages infected with Citrobacter rodentium - Hugo, Ayelén (2017)
Citrobacter rodentium is a specific murine enteropathogen which causes diarrheal disease characterized by colonic hyperplasia and intestinal inflammation. Recruitment of neutrophils and macrophages constitute a key step to control the infection. Since modulation of the activity of professional phagocytic cells could contribute to improve host´s defences against C. rodentium, we investigated the effect of Lactobacillus delbrueckii subsp. lactis (strain CIDCA 133) on the interaction between murine macrophages (RAW 264.7) and C. rodentium. Phagocytosis, surface molecules and inducible nitric oxide synthase (iNOs) expression were determined by flow cytometry. Reactive oxygen species (ROS) were assessed by fluorescence microscopy. The presence of lactobacilli increased phagocytosis of C. rodentium whereas C. rodentium had no effect on lactobacilli internalization. Survival of internalized C. rodentium diminished when strain CIDCA 133 was present. CD-86, MHCII, iNOs expression and nitrite production were increased when C. rodentium and lactobacilli were present even though strain CIDCA 133 alone had no effect. Strain CIDCA 133 led to a strong induction of ROS activity which was not modified by C. rodentium. Lactobacillus delbrueckii subsp. lactis (strain CIDCA 133) is able to increase the activation of murine macrophages infected with C. rodentium. The sole presence of lactobacilli is enough to modify some stimulation markers (e.g. ROS induction) whereas other markers require the presence of both bacteria; thus, indicating a synergistic effect.